Standar Kerja dan Perencanaan Kualitas Potongan Daging Sapi dari RPH Sampai Display Pasar Tradisional - Kelvin Siswanto; I Nyoman Sutapa (Jurnal Titra, 2015)
Rumah Potong Hewan (RPH) is a place where do slaughter animals for food. Consumer demand for quality piece of meat made RPH must pay attention to the production process. Standardized work and quality plan is needed for the resulting product had a high quality, especially piece of meat. Standardized work and quality plan is not end until RPH, but also transportation and display at traditional market. Improvement methods used in this research is the method of Standardized work, quality plan, and fishbone diagram. This improvement will be supported by the establishment of some standardization work in order to maintain sustainable improvements in the future.